Homologies of floral structures in velloziaceae with particular reference to the corona - Das Graças Sajo, Maria [UNESP]; De Mello-Silva, Renato; Rudall, Paula J. (University of Chicago Press, 2010)
New data on floral morphology, development, and vasculature in two Brazilian genera of the monocot family Velloziaceae (Pandanales) are used to explore the homologies of their unusual floral structures, especially the corona of Barbacenia and the corona-like appendages and multiple stamens of some Vellozia species. All Velloziaceae have epigynous flowers. Some species of Vellozia are polyandrous, and stamen number can be variable within species. In Vellozia jolyi, there is a single stamen opposite each sepal and a stamen fascicle (of three secondary stamens) opposite each petal. Each stamen possesses a single vascular bundle, and these are united into a single aggregate bundle in proximal regions of the fascicle. Stamens mature centripetally within each fascicle. The coronal appendages of both genera are closely associated with the stamens, but they share some vasculature with the tepals and develop late in ontogeny. The coronal organs cannot readily be homologized with any of the typical floral organs, but they show partial homology with both tepals and stamens. They are most readily interpreted as a late elaboration of the region between the petals and stamens associated with epigyny and the hypanthium. © 2010 by The University of Chicago. All rights reserved.
Keywords: Corona; Flower; Monocot; Pandanales; Velloziaceae; corona; floristics; homology; monocotyledon; morphology; ontogeny; physiological response; Barbacenia; Vellozia